The Effect of Business Financing Models on BTPN Syariah Bank Performance - Khalil, Jafril; Suwanto, Wawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of the financing business model on the performance of BTPN syariah banks. The design or method used in this study is a quantitative approach with regression analysis. This method uses secondary data that is used to find the relationship between the business model and the success of the bank's performance level by using financial report data for 2016 to 2020 quarterly. Performance measurement is carried out to determine the direct relationship of the influence of non-financing on customer performance on the performance of BTPN Syariah banks as seen from the analysis of profit ratios and NPF. The results of the study indicate that the Joint Responsibility Financing conducted by Bank BTPN Syariah does not significantly affect the increase or decrease in Non Performing Financing (NPF) of Bank BTPN Syariah. This is evidenced by the value of the coefficient of determination obtained is only 17%. The Joint Responsibility Financing conducted by Bank BTPN Syariah has a significant impact on increasing profits at Bank BTPN Syariah. This is evidenced by the value of the coefficient of determination obtained by 41.9%.